Aggregatibacter Actinomycetemcomitans With Periodontitis and Rheumatoid Arthritis - Yizhi Huang; Su Ni (Elsevier, 2024)
ABSTRACT: Objective: The aim of this work was to explore the association between Aggregatibacter actinomycetemcomitans (A actinomycetemcomitans) infection and disease activity amongst those with rheumatoid arthritis (RA) with or without periodontitis (PD) in a Chinese population. Methods: A case-control study was conducted from November 2017 to March 2019. The correlation coefficients between A actinomycetemcomitans positivity and RA-related examination indicators as well as periodontal examination parameters were calculated by using the Spearman correlation analysis. Results: A total of 115 patients with RA were recruited: 67 patients with RA only and 48 with RA + PD. The percentage of A actinomycetemcomitans positivity was significantly higher in the RA + PD group compared with the RA-only group (P = .007 for positive percentage; P = .020 for percentage of A actinomycetemcomitans positivity in the total oral microbiome). Furthermore, RA-related measures such as Disease Activity Score 28, rheumatoid factor, anticyclic citrullinated peptide, and anticitrullinated protein antibodies were all positively correlated with the percentage of A actinomycetemcomitans positivity (P range: .002∼.041). In addition, significant correlations were observed amongst A actinomycetemcomitans positivity and probing pocket depth (P = .027) and gingival index (P = .043), whereas null correlations were found amongst the percentage of A actinomycetemcomitans positivity and plaque index (P = .344), clinical attachment loss (P = .217), and bleeding on probing (P = .710). Conclusions: A actinomycetemcomitans infection may be related to the development of PD amongst patients with RA.